Studi Evaluasi Intensitas Pencahayaan Kamar Operasi RSUP Dr. M. Djamil Padang Sesuai Standar Nasional Akreditasi Rumah Sakit (SNARS) - Andi Syofian; Sari Marlisa (Jurnal Teknik Elektro, 2019)
General Hospital (RSUP) Dr. M. Djamil Padang is a class-A education hospital with the status of a Public Service Agency (BLU). As a hospital health care facility must maintain the quality of plenary services provided by medical personnel, both in terms of the quality of the physical environment and the quality of environmental health, one of them is the intensity of lighting. This study was to evaluate the intensity of lighting to minimize nosocomial infection in the operating room of Dr. M. Djamil Padang hospital based on National Standards for Hospital Accreditation by measuring directly to the study location and comparing with the results of calculations, then adjusted to Kepmenkes RI Standard number: 1204 / MENKES / SK / 2004 where for general operating rooms 300-500 lux, while for 10,000-20,000 lux operating lamps. From the measurement results and the results of calculations carried out it is known that between the intensity of the lighting with the large room is inversely proportional to the larger the room the resulting lighting intensity will be smaller, and vice versa the smaller the room the greater the intensity of lighting.